Energetic Materials From Cradle to Grave - Shukla, Manoj K.; Boddu, Veera M.; Steevens, Jeffery A.; Damavarapu, Reddy; Leszczynski, Jerzy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a comprehensive account of energetic materials, including their synthesis, computational modeling, applications, associated degradation mechanisms, environmental consequences and fate and transport. This multi-author contributed volume describes how armed forces around the world are moving their attention from legacy explosive compounds, which are heat and shock sensitive (thus posing greater challenges in terms of handling and storage), to the insensitive munitions compounds/formulations such as insensitive munitions explosive (IMX) and the Picatinny Arsenal Explosive (PAX) series of compounds. The description of energetic materials focuses on explosives, pyrotechnic compositions, and propellants. The contributors go on to explain how modern generation energetic compounds must be insensitive to shock and heat but at the same time yield more energy upon explosion. Nanoinspired and/or co-crystallized energetic materials offer another route to generate next-generation energetic materials, and this authoritative book bridges a large gap in the literature by providing a comprehensive analysis of these compounds. Additionally, it includes a valuable overview of energetic materials, a detailed discussion of recent advances on future energetic compounds, nanotechnology in energetic materials, environmental contamination and toxicity, assessment of munitions lethality, the application quantitative structure-activity relationship (QSAR) in design of energetics and the fate and transport of munition compounds in the environment.
Historical Account of Energetic Materials - Past, Present and Future -- Munitions Safety and Modern Approach -- Synthesis of Energetic Materials.-Bottom Up and Top Down Approaches to Assessment and Decision Support for Energetic Materials -- Design of Energetics and Munitions for Demilitarization.-Scaling of Energetic Compounds - From Laboratory to Industry -- Quantum Mechanical Calculations of Structures and Properties of Energetic Compounds -- Multiscale Modeling of Energetic materials -- Nanoenergetic - Present and Future Direction -- Energetic Properties of High Performance Energetic Material System -- High Pressure Phenomena in Energetic Materials -- Life-Cycle Analysis of Energetic Compounds -- Environmental Consequences of Energetic Compounds -- Fate and Transport of Energetic Materials Release and Exposure of Energetic Compounds -- Energetic Material Induced Environmental Toxicity -- QSAR Approach Predicting Environmental Toxicity of Explosive Compounds -- Hydrolysis of Explosive Compounds.-Photodegradation of Explosive Compounds -- Environmental Remediation of Contamination due to Energetic Compounds.
Keywords: Chemistry, Physical and theoretical; Materials -- Analysis; Security systems; Environmental monitoring; Theoretical Chemistry; Characterization and Analytical Technique; Security Science and Technology; Environmental Monitoring